Therapeutic drug monitoring of voriconazole and the impact of inflammation on plasma trough concentrations in children - Hu, Lin; Wang, Changyu; Tang, Xi; Huang, Qi; Li, Yanfei; Huang, Shiqiong (Frontiers in Pharmacology, 2025)
The aim of this study was to investigate the factors influencing voriconazole (VRC) plasma trough concentrations (Ctrough) in children and to provide a scientific basis for individualized VRC dosing. A retrospective study was conducted on children aged ≤18 years who received VRC treatment between 1 December 2017, and 31 December 2022. Medical data were collected to examine the relationship between VRC Ctrough and non-genetic factors. A total of 59 patients were included in the study, with 90 VRC Ctrough analyzed. The median patient age was 13 years (range, 1–18 years), and the median weight was 37.9 kg (range, 10.0–77.7 kg). The median number of VRC Ctrough measurements per patient was 1 (range, 1–10). Inflammation, as indicated by C-reactive protein (CRP) levels, was significantly associated with dose-adjusted VRC Ctrough (Ctrough/D) (n = 90, r = 0.746, P < 0.001). Patients with severe inflammation had significantly higher VRC Ctrough/D compared to those with mild inflammation (P = 0.001). The proportion of supratherapeutic concentrations was highest in the severe inflammation group, significantly higher than in the mild inflammation group (41.7% vs. 11.9%; P = 0.037). A significant correlation was found between VRC Ctrough/D and CRP concentrations in patients aged ≥12 years (n = 54, r = 0.784, P < 0.001), but no correlation was observed in patients aged <12 years (n = 36, r = 0.199, P = 0.244). A linear mixed model demonstrated a significant association between VRC Ctrough/D and CRP (β = 0.448; 95% CI, 0.309–0.587). Additionally, total bilirubin (TBil) (P = 0.039), direct bilirubin (DBil) (P = 0.034), albumin (ALB) (P = 0.011), and serum creatinine (Scr) (P = 0.008) were significantly associated with VRC Ctrough/D. These findings indicate that CRP levels should be considered a key factor influencing VRC exposure in pediatric patients. The relationship between VRC Ctrough and CRP levels varies across age groups and should be analyzed separately.